Interkalasi Ion Mefenamat pada Host Mg/Al Hidrotalsit sebagai Rancangan Obat Lepas Lambat - Fajar Indah Puspita Sari (Syarif Hidayatullah State Islamic University, 2018)
The aim of this study was to intercalate mefenamic ions in the interlayer structure of Mg/Al hydrotalcite and to test the release of mefenamic ion from host hydrotalcite interlays to determine its potential as a slow release drug design. Intercalation of mefenamic ions into interlayer structure of Mg/Al hydrotalcite by ion exchange has been studied. This success intercalation was confirmed by XRD data, diffractogram before and after intercalation showed a shift of d003, d006 and d009. The change of d003 from 8.717 Å to 22.017 Å indicates that the mefenamic ion has entered the interlayers of hydrotalcite. The FTIR analysis confirms that the nitrate ion was successfully replaced by mefenamic ions in the hydrotalcite interlayer. FTIR data indicate the absorption of symmetry and asymmetry of carboxylic groups in 1381 and 1612 cm-1 of the mefenamic ion. Have studied ion exchange kinetics and release of mefenamic ions from hydrotalcite hosts to determine their potential as a slow-release drug design. The result show mefenamic ion can be released from the hydrotalcite host for 6 hours. So that Mg / Al hydrotalcite has the potential to be used in slow release drug design.